DEVELOPMENT OF SCIENTIFIC APPROACH BASED STUDENT WORKSHEET ON ANIMAL TOPICS FOR 10th GRADE - Adriana YD Lumban Gaol; Natalia Sihombing; Erlintan Sinaga (Universitas Negeri Medan, 2022)
This study aims to design and produce Student Worksheets (LKPD) based on the Scientific Approach for animalia material for 10th-grade students in SMA Yayasan Perguruan Utama Medan. The research used a research and development methodology. The design of the Scientific Approach-based LKPD was carried out using the 4-D development model, namely Define, Design, Development, and Disseminate. The research results show that the developed LKPD based on the scientific approach received a